2016
DOI: 10.1186/s12879-016-1601-4
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection, viral hepatitis and liver fibrosis among prison inmates in West Africa

Abstract: BackgroundPrisoners represent a vulnerable population for blood-borne and sexually transmitted infections which can potentially lead to liver fibrosis and ultimately cirrhosis. However, little is known about the prevalence of liver fibrosis and associated risk factors among inmates in sub-Saharan Africa.MethodsScreening of liver fibrosis was undertaken in a randomly selected sample of male inmates incarcerated in Lome, Togo and in Dakar, Senegal using transient elastography. A liver stiffness measurement ≥9.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 43 publications
7
32
3
Order By: Relevance
“…Hazardous alcohol consumption affected over 10% of the study population in Zambia, Côte d'Ivoire and Togo, but was uncommon in Senegal (0.9% of participants), where the large majority of the population is Muslim. We previously found similar estimates in a study among 680 prison inmates in Senegal and Togo: 12% of prisoners in Lomé reported hazardous drinking versus 5% in Senegal . Similar differences in alcohol consumption patterns were found in Tanzania: alcohol consumption was less common in adolescents of Muslim faith compared to others, independent of the region where the survey was conducted .…”
Section: Discussionsupporting
confidence: 77%
“…Hazardous alcohol consumption affected over 10% of the study population in Zambia, Côte d'Ivoire and Togo, but was uncommon in Senegal (0.9% of participants), where the large majority of the population is Muslim. We previously found similar estimates in a study among 680 prison inmates in Senegal and Togo: 12% of prisoners in Lomé reported hazardous drinking versus 5% in Senegal . Similar differences in alcohol consumption patterns were found in Tanzania: alcohol consumption was less common in adolescents of Muslim faith compared to others, independent of the region where the survey was conducted .…”
Section: Discussionsupporting
confidence: 77%
“…We included all individuals diagnosed with an HBV infection in a cross‐sectional prevalence study among vulnerable populations in West Africa. Inmates incarcerated in state prisons in Lome, Togo (September‐October 2013) and Dakar, Senegal (April‐May 2014) were initially recruited . FSW and MSM were subsequently recruited in a dedicated clinic located in Abidjan, Cote d'Ivoire (November 2014‐April 2015) .…”
Section: Methodsmentioning
confidence: 99%
“…FSW and MSM were subsequently recruited in a dedicated clinic located in Abidjan, Cote d'Ivoire (November 2014‐April 2015) . Inmates were randomly selected based on a cluster sampling approach using the prison cell as the statistical unit as previously described . FSW and MSM were randomly selected using a systematic sampling approach.…”
Section: Methodsmentioning
confidence: 99%
“…One study conducted among people living with HIV in 2011 estimated the HBV prevalence at 9.7% [4]. Another study among prisoners in 2013 estimated the prevalence at 12.5%, while a study among individuals in a hospital in Lomé found a prevalence as high as 19.1% [5] [13]. However, no study in Togo has so far specifically focused on the prevalence of HBV among youth and university students, who could be considered a vulnerable population.…”
Section: Introductionmentioning
confidence: 99%
“…Sub-Saharan Africa (SSA) has the highest prevalence of Hepatitis B with 80 million people carriers of HBV [4] and a prevalence ranging from 5% to 10% in the adult population [1]. Despite HBV prevalence being relatively high in SSA, screening and treatment is still limited or rare in this region [5].…”
Section: Introductionmentioning
confidence: 99%